Effectiveness of Backward and Forward Linkages in Fruit Cultivation: A study of NERAMAC (North Eastern Regional Agricultural Marketing Corporation Limited) (Indian Journal of Extension Education, 2015)
NERAMAC, a public sector organisation was set up to support fruit producers of north eastern India in fruit cultivation, marketing, processing and employment generation. It thereby bridges the gap between the farmers and the market to enhance the agricultural procurement, processing, and marketing infrastructure. The effectiveness of NERAMAC in technology advisory service, input delivery services and marketing services in Dhubri and Karimganjdistrict of Assam were studied. An ex-post facto research design was used for the study and the data were collected from 120 respondents comprising of 80 beneficiary farmers and 40 non-beneficiary farmers of NERAMAC. The effectiveness was measured through effectiveness index developed for this purpose. The extension services in respect of backward and forward linkages rendered by NERAMAC were found to be medium in effectiveness by majority of the farmers in the region.